Management of a giant pleomorphic adenoma of the palate: Case report - Babacar Tamba; Mamadou Diatta; Mouhammad Kane; Baidy Lo; Abdou Ba; Soukeye Dia Tine (Elsevier, 2021)
Pleomorphic adenoma of the accessory salivary glands represents 60% of oral salivary tumors. Clinically it presents as a slow growing, painless swelling covered by a healthy mucosa. Its preferential location in the accessory salivary glands is the palate region.We report the case of a 61-year-old female patient who was referred for a swelling of the palate. The swelling measured approximately 40 mm in long axis, was firm to elastic, painless, did not bleed on contact and was covered by a healthy mucosa. The radiographic examination revealed an isodense, homogeneous, well-limited tissue process in the palatal vault and concluded that it was a palatal tumor measuring 47 × 35 × 24mm with benign characteristics. The removal of the encapsulated tumor was performed under general anesthesia. The postoperative course was simple. A prosthetic rehabilitation was performed two months later. No recurrence was observed after six months.